Divergently Transcribed ncRNAs in Escherichia coli: Refinement of the Transcription Starts Assumes Functional Diversification - Kiselev, Sergey; Markelova, Natalia; Masulis, Irina (Frontiers in Molecular Biosciences, 2021)
Non coding regulatory RNAs comprise specialized group of essential genetically encoded biological molecules involved in the wide variety of cellular metabolic processes. The progressive increase in the number of newly identified ncRNAs and the determination of their genome location obviously indicates their predominant nesting in intergenic regions (IGRs) and the possibility of expression under the control of their own regulatory elements. At the same time, the regulation of ncRNA’s transcription cannot be considered in isolation from the processes occurring in the immediate genetic environment. A number of experimental data indicate the notable impact of positional regulation of gene expression mediated by dynamic temporal DNA rearrangements accompanying transcription events in the vicinity of neighboring genes. This issue can be perceived as particularly significant for divergently transcribed ncRNAs being actually subjected to double regulatory pressure. Basing on available results of RNAseq experiments for Escherichia coli we screened out divergent ncRNAs and the adjacent genes for the exact positions of transcription start points (TSPs) and relative efficiency of RNA production. This analysis revealed extension or shortening of some previously annotated ncRNAs resulting in modified secondary structure, confirmed stable expression of four ncRNAs annotated earlier as putative and approved the possibility of expression of divergently transcribed ncRNAs containing REP elements. The biogenesis of secreted sRNAs from divergently transcribed ncRNAs Ffs, ChiX, RalA and RyhB are discussed taking into account TSPs’s positions. Refinement of TSPs for neighboring genes renders some ncRNAs as true antisense overlapping with 5’UTR of divergently transcribed mRNAs.